2001
DOI: 10.1002/jcb.1227
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of connexin43 gap junctional intercellular communication by TPA requires ERK activation

Abstract: The phorbol ester, 12-O-tetradecanoylphorbol-13-acetate (TPA), is a potent inhibitor of gap junctional intercellular communication (GJIC). This inhibition requires activation of protein kinase C (PKC), but the events downstream of this kinase are not known. Since PKC can activate extracellular signal regulated kinases (ERKs) and these also downregulate GJIC, we hypothesized that the inhibition of GJIC by TPA involved ERKs. TPA treatment (10 ng/ml for 30 min) of WB-F344 rat liver epithelial cells strongly activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
70
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(79 citation statements)
references
References 26 publications
9
70
0
Order By: Relevance
“…15). In accordance with published data (26)(27)(28)(29), TPA induced Cx43-GFP internalization, as the majority of Cx43-GFP was found in intracellular compartments (Fig. 4A, arrowheads) previously identified as early and late endosomes, as well as lysosomes (30).…”
Section: Resultssupporting
confidence: 92%
“…15). In accordance with published data (26)(27)(28)(29), TPA induced Cx43-GFP internalization, as the majority of Cx43-GFP was found in intracellular compartments (Fig. 4A, arrowheads) previously identified as early and late endosomes, as well as lysosomes (30).…”
Section: Resultssupporting
confidence: 92%
“…16,17 Furthermore, MAPK activation and Cx43 downregulation may be connected, as constitutively activated p-jnk potently reduces Cx43 levels in mouse myocardium, and p-erk has been implicated in Cx43 downregulation in liver epithelial cells. 18,19 Ongoing studies are addressing the physiological importance of the expression changes revealed in the present study, as well as expanding the analysis by means of subproteomic and transcriptome analysis.…”
Section: Discussionmentioning
confidence: 97%
“…Because MAPK activation has been proposed to be involved in relocalization of Cx43 from the plasma membrane to intracellular membranes in response to phorbol esters and growth factors (e.g. Leithe and Rivedal, 2004;Ruch et al, 2001;Sirnes et al, 2008) and phosphorylation at S279 or S282 has been proposed to be involved in association with NEDD4 and turnover of Cx43 (Leykauf et al, 2006), we decided to examine the levels of phosphorylated S279 and/or S282 (pS279/282) during this TPA treatment time course. We found that the level of pS279/282 peaked at 15-30 minutes (Fig.…”
Section: Interaction Between Zo-1 and Cx43 Is Eliminated By S373 Phosmentioning
confidence: 99%